Flavonoid isolated from the stems of Melastoma candidum D. Don collected in Vietnam. - Hà, Trần Thanh; Hà, Nguyễn Thị; Cương, Mai Văn (Vietnam Journal of Chemistry, 2014)
A phytochemical fractionation of the ethyl acetate extract of the stems of Melastoma candidum D. Don led to the isolation of two flavonoids. By means of the spectrocopic methods including MS, NMR, the isolated compounds were determined to be quercetin, quercitrin.